Pementasan Barong Dan Rangda Dalam Perspektif Estetika Dan Pendidikan Agama - I Made Suta (Institut Seni Indonesia Denpasar, 2009)
Barong and Rangda that are performed in the temple are secred. The performance of Barong and Rangda is usually on Saturday Kliwon, Kuningan according to Balinese calendar. People believe that if Barong and Rangda are not performed, it will be epidemic disaster (grubug). The performance of Barong and Rangda are full of aesthetical values such as its ornaments, movement, and accessories used in the performance. All are bind in Three Wisesa : Satyam (Truth), Siwam (Purity), and Sundaram (beauty). The performance of Barong and Rangda also have religious, magic, social, harmony, and balance dimension. In the perspective of Hindu education the performance of Barong and Rangda teach Sraddha (faith), Tattwa (philosophy), and Susila (ethnic).